Antimicrobial Treatment Challenges in the Management of Infective Spondylodiscitis Associated with Hemodialysis: A Comprehensive Review of Literature and Case Series Analysis - Ioana A. Ratiu; Corina F. Moisa; Laura Țiburcă; Edy Hagi-Islai; Anamaria Ratiu; Gabriel Cristian Bako; Cristian Adrian Ratiu; Liana Stefan (MDPI AG, 2024)
Infective spondylodiscitis (ISD), the infection of vertebral bodies and surrounding tissues, is a rare complication with major impact on the long-term survival of hemodialysis (HD) patients. Although the most frequent etiology is staphylococcal, identifying these pathogens in blood cultures and biopsy cultures is often difficult. This paper aims to present suitable antibiotic combinations for the treatment of these patients, which is usually challenging in the case of an unidentified pathogen. We presented the therapies applied for 13 HD patients and 19 patients without chronic kidney disease (CKD), diagnosed with ISD between 2013 and 2023 in Bihor County. The percentage of positive blood cultures was low in both groups (30.78% HD vs. 15.78% non-HD). The average length of antibiotic therapy was 5.15 weeks in HD patients and 6.29 weeks in non-HD patients. The use of Carbapenem alone (e.g., Meropenem) for an average of 19.6 days for patients in HD when the pathogen was not identified has proven to be efficient in most cases, similarly to using Vancomycin and Fluoroquinolone/Cephalosporines in combination. Regarding the non-CKD patients, the use of Clindamycin in various combinations for an average of 30.3 days has proven to be efficient in more than 90% of cases of ISD with a nonidentified pathogen. Within 2 years after ISD was diagnosed, 12 of the 13 HD patients passed away, mainly due to cardiovascular causes. Unfortunately, there are no guidelines in the literature concerning the empiric treatment of ISD in the particular case of HD patients. Upon checking the literature on PubMed and Google Scholar, only 10 studies provided relevant data regarding ISD treatment for HD patients. More data about the treatment and evolution of these patients is needed in order to elaborate a truly relevant metanalysis.